Cooperation of Kazakhstan and India in the Field of Science This - Тaировa, Д. Н. (Journal of Oriental Studies, 2018)
This article examines the ways of development of science of the two countries in the context of mutually beneficial cooperation between Kazakhstan and India in the field of science. The main areas of science development and their beneficial use for the opposite side are analyzed. Two countries India and Kazakhstan, which are at different levels of development, find common ground and profitable use of available resources.